Smart control and seismic analysis of concrete frames with piezoelectric layer based on mathematical modelling and numerical method. (August 2021) - Karegar, Masoud; Bidgoli, Mahmood Rabani; Mazaheri, Hamid
Abstract: The dynamic analysis of a concrete frame with smart layer under earthquake load is investigated in this paper. The optimization analysis of this structure is based on Grey Wolf algorithm (GWO) which obeys form the leadership hierarchy and hunting mechanism of grey wolves. The mathematical theory of hyperbolic shear deformation (HSDT) is used for modelling the planar frame. The structure energies include kinetic energy, potential energy, and external works are obtained by strain–displacement and stress–strain relations. Then, the governing equations of the frame are derived using the Hamilton's principle. applying these relations, the response of the concrete frame under earthquake load is investigated using the numerical methods of differential quadrature (DQ) and Newark. The main objective of this paper is to investigate the effects of the external voltage, thickness of smart layer, boundary conditions; geometrical parameters of frame and structural damping on the seismic displacement of the frame. The results shown that by applying negative external voltage, the maximum dynamic displacement of the frame lessens. It can be found that with applying the positive voltage, the optimum deflection of the system increases.